Updosing nonsedating antihistamines in patients with chronic spontaneous urticaria: a systematic review and meta-analysis - Guillén-Aguinaga, S.; Jáuregui Presa, I.; Aguinaga-Ontoso, E.; Guillén-Grima, F.; Ferrer, M. (British journal of dermatology (1951), 2016)
Summary There is a lack of large, randomized, double‐blind studies that address antihistamine updosing for chronic spontaneous urticaria (CSU). The objective of this systematic review is to explore and analyse available data to provide clinical evidence for the efficacy of antihistamine updosing. We searched the literature in Medline, Scopus, Google Scholar, Embase, Web of Science and Cochrane databases using the keywords ‘chronic, urticaria, antihistamines’ to identify studies published between January 1990 and November 2014. We assessed quality using the Jadad score that evaluates quality of randomization, double‐blinding and losses to follow‐up. We identified 1042 articles and 15 articles were included in the final evaluation. We performed two meta‐analyses, one that included studies that analysed treatment response among groups receiving different antihistamine dosages vs. placebo, and another that analysed antihistamine updosing in those patients who did not respond to standard dosages. Only five articles obtained a high quality level score. We did not find significant differences in response rates or number of weals in those patients who received a standard dosage vs. a high dosage. We found a significant improvement only in the pruritus variable of the Urticaria Activity Score scale. The estimated relative risk for improvement by increasing the antihistamine dosage was 2·27 [95% confidence interval (CI) 1·68–3·06]; however, there was significant heterogeneity. The proportion of nonrespondent patients with CSU who responded to antihistamine updosing was 63·2% (95% CI 57–69·6). We found that updosing antihistamines significantly improved control of pruritus but not weal number. However, the relative weakness of the studies and the significant heterogeneity among them made it difficult to reach a final conclusion. What's already known about this topic? Antihistamines represent the first‐line therapy for chronic spontaneous urticaria (CSU). In spite of their efficacy, CSU remains uncontrolled in a high percentage of patients receiving regular doses of antihistamines. Guidelines for the management of CSU recommend updosing antihistamines up to fourfold as a second‐line therapy. What does this study add? This is the first meta‐analysis on updosing antihistamines for the treatment of CSU. In spite of the high recommendation, updosing antihistamines significantly improves control of pruritus but not weal number. There is a great need for large well‐performed studies on this subject as the present studies that support updosing are relatively weak and have a high level of heterogeneity. Linked Comment: Weller and Maurer. Br J Dermatol 2016; 175:1134–1135.